İsyan Günlerinde Aşk - Karaca, Alaattin (Kitabevi, 2002)
This book is a novel taking its subject from the power dispute between Committee of Umon and Progress and Abdulhamit II during Second Constitutional Period in the framework of 31th March Rebellion. In the novel apart from historical context, the theme of love also constitutes a significant place. Ahmet Altan's novel has been widely discursed in the media lately because it has dealt with the 31th March Rebellion, an important historical event of our near current history, Fram a different perspective. In this study, Love in the Days of Rebellion is to be studied from a literary svope than from political disputes.
Love in the Days of Rebellion
Keywords: 31th March Rebellion; Second Constitutional Period; Commitee of Union and Progress; Abdulhamit II